Effective Treatment of Veterans With PTSD: Comparison Between Intensive Daily and Weekly EMDR Approaches - Hurley, E. C. (Frontiers in Psychology, 2018)
Word count: 361 The effectiveness of EMDR therapy in treating veterans diagnosed with PTSD was evaluated in this study using two treatment formats: intensive daily EMDR treatment provided twice a day during a 10-day period and a second format of one session each week. The study used archived outcome data previously collected and stored at Soldier Center. Both formats provided 18-20 treatment sessions of EMDR therapy to veterans diagnosed with PTSD that included dissociative exhibitions and moral injury issues. Questions addressed included: (1) does EMDR therapy administered twice daily ameliorate veterans’ PTSD symptoms; (2) does EMDR therapy administered twice daily provide equivalent outcome results as EMDR therapy administered weekly for 18-20 sessions -; and (3) does the treatment outcome persist. The effectiveness of the weekly treatment group was also evaluated. Both groups’ results were assessed at pre-treatment, post-treatment and one-year follow-up. The results indicated that both weekly treatment and intensive daily treatment groups produced statistically significant treatment effects (p < .001) that were maintained at one-year follow-up. The10-day EMDR intensive daily treatment (EMDR therapy twice a day for 10 days) produced a similar outcome as to that of the weekly treatment with a one-year follow-up. Results support the effectiveness of EMDR therapy when offered in both weekly treatment format as well as the intensive 10-day format on an outpatient basis. While recognizing the limitations of this study the results are significant to warrant additional research.